Pandangan Quraish Shihab dan Faqihuddin Abdul Kodir tentang Hukum Nusyuz - Andriani, Farika; Al awwali, Habib Busyro; Abrori , Ahmad Sahal Aqil; Rohmah, Elva Imeldatur (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2022)
Abstract: This article discusses the views of Quraish Shihab and Faqihuddin Abdul Kodir on nusyuz law. This research uses literature research methods. Research data is collected through literature collection and then analyzed by comparative techniques. The study results concluded that according to Quraish Shihab, the concept of Nusyuz is defiance and disobedience to the rights of Allah and the rights of the husband. While the concept of Nusyuz in the view of Faqihuddin Abdul Kodir is, Nusyuz is the opposite of obedience. That is, all negative actions in husband and wife relationships weaken the pair bond between husband and wife so that they become far from the conditions of sakinah, mawaddah, and rahmah. Either done by the wife to the husband or done by the husband to the wife. Keywords: Nushuz, Islamic law, husband, wife. Abstrak: Artikel ini membahas pandangan Quraish Shihab dan Faqihuddin Abdul Kodir mengenai hukum nusyuz. Penelitian ini menggunakan metode penelitian kepustakaan. Data dikumpulkan melalui pengumpulan bahan pustaka dan kemudian dianalisis dengan teknik perbandingan. Hasil penelitian menunjukkan bahwa dalam pandangan Quraish Shihab, konsep nusyuz merujuk pada tindakan pembangkangan dan ketidakpatuhan terhadap hak-hak Allah dan hak-hak suami. Di sisi lain, dalam pandangan Faqihuddin Abdul Kodir, konsep nusyuz didefinisikan sebagai tindakan negatif dalam hubungan suami-istri yang merusak ikatan antara keduanya, sehingga menjauhkan mereka dari keadaan sakinah, mawaddah, dan rahmah. Hal ini bisa terjadi baik dari pihak istri terhadap suami maupun sebaliknya, yaitu suami terhadap istri. Kata Kunci: Nusyuz, Hukum Islam, Suami, Istri.